Pemulihan Citra Diri Remaja Madya: Integrasi Psikologi dan Teologi - Mudak, Sherly; S. Manafe, Ferdinan (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
This article aims to explain how the integration of psychology and theology can be used as a method of self-image restoration for middle-aged adolescents. This qualitative descriptive research aims to describe in words the purpose of integrating psychology and theology to help middle adolescents improve their self-image. This research was conducted by collecting data from scientific journals and other references in accordance with the topic of writing. The results show that the integration between psychology and theology can help middle adolescents to improve their self-image. This integration combines psychological theories and theological views that can help middle adolescents understand themselves and acquire strong moral and spiritual values to improve their self-image. Some techniques and strategies applied in the integration of psychology and theology can help middle adolescents overcome self-image problems and improve their quality of life. This research can be an important reference for professionals in the fields of psychology and theology, as well as parents and counselors who want to help middle adolescents improve their self-image. Artikel ini bertujuan untuk menjelaskan bagaimana integrasi antara psikologi dan teologi dapat digunakan sebagai metode pemulihan citra diri remaja madya. Tujuan riset dengan metode penelitian kualitatif deskriptif ini untuk mengintegrasikan psikologi dan teologi guna menolong remaja madya memperbaiki citra diri. Penelitian ini dikakukan dengan mengumpulkan data dari jurnal ilmiah dan referensi lain sesuai dengan topik penulisan. Hasil penelitian menunjukkan bahwa integrasi antara psikologi dan teologi dapat membantu remaja madya untuk memperbaiki citra diri mereka. Integrasi ini menggabungkan teori-teori psikologi dan pandangan-pandangan teologi yang dapat membantu remaja madya memahami diri mereka sendiri dan memperoleh nilai-nilai moral dan spiritual yang kuat untuk memperbaiki citra diri mereka. Beberapa teknik dan strategi yang diterapkan dalam integrasi psikologi dan teologi dapat membantu remaja madya mengatasi masalah citra diri dan meningkatkan kualitas hidup mereka. Penelitian ini dapat menjadi referensi penting bagi profesional di bidang psikologi dan teologi, serta orang tua dan konselor yang ingin membantu remaja madya dalam memperbaiki citra diri mereka.